Biolubricant Production from Stearic Acid and Residual Secondary Alcohols: System and Reaction Design for Lipase-Catalyzed Batch and Continuous Processes - Lima, Rosemar de; Bento, Heitor B. S. [UNESP]; Reis, Cristiano E. R.; Vilas Boas, Renata N.; Freitas, Larissa de; Carvalho, Ana K. F.; Castro, Heizir F. de (Springer, 2021)
Six lipases were immobilized on a styrene-divinylbenzene support and evaluated on the batch esterification reaction of stearic acid with fusel oil. After a screening design, the two most appropriate lipases were assayed on a packed-bed system, achieving high conversion rates (90-93%) and productivities of isoamyl stearate up to 3144 mmol g(-1) min(-1), which can be used as a substitute to fossil-derived lubricants. Graphic
Keywords: Enzymatic catalysis; Heterogeneous catalysis; Immobilization